UNIVERSITY AS A NETWORK CENTER FOR VOCATIONAL GUIDANCE AND SOCIALIZATION OF AN INDIVIDUAL - Roman G. Strongin; Evgeni V. Chuprunov (Высшее образование в России)
Vocational guidance at school and at university has today be substantially advanced to support forestall education because of fast accelerating development in science and technology. This paper presents some new forms of such vocational guidance activities generated by the experience of National Research Lobachevski State University ofNizhni Novgorod (UNN). These activities are university educational cluster, university school, university «Science Park», student's Forum «Career+», projects «The Path of Success», «School of Career Development», «Primary Academy of State Governance ». The article also characterizes UNN contribution into Russian School Olympic Movement and into support programs for talented children. Implementation of all such projects involving students and schoolchildren from many educational establishments generates the need in providing mass participation of university partners-employers. As a result, the university has to control the vast emerging dynamic network that requires some new style of management.